(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the chlorophyll-α, chlorophyll-β and carotenoids in the leaf content of local and foreign varieties and samples of sorghum obtained from the international organization ICBA and the collection of the Scientific and Experimental Station of Fodder Crops of the Republic of Uzbekistan.